The Defence of Doctoral Thesis, calling for a Notebook (About the Doctoral Thesis and its Defence of Aurimas Švedas "Soviet Lithuanian Historiography: Official Discourse and its Altematives (1944-1985)" - Aurelijus Gieda (Lietuvos Istorijos Studijos)
-